Impact of forest degradation on soil properties in the Peruvian Amazon - Vallejos Torres, Geomar (2026)
Background: The Amazonian forests are increasingly threatened due to continuous changes in land use, particularly deforestation. This study aimed to quantify and analyze the vertical distribution of soil glomalin and its relationship with carbon, climate, and soil properties across three forest types of the Peruvian Amazon. A total of 18 plots were selected and sampled in forests with different vegetation cover types: deforested, disturbed, and primary forest. The vertical variation of total glomalin (TG), easily extractable glomalin (EEG), and the number of arbuscular mycorrhizal fungal (AMF) spores was estimated, as it was the relationships of these variables with soil depth, physical-chemical properties, and climate conditions. Results: The mean values for TG, EEG, and AMF showed vertical variations in the three forest cover types, with high values in disturbed forests and degraded soils. Overall, higher mean values were found in the surface soil layers compared to the deep layers. TG, EEG, and AMF were positively corelated with soil organic carbon (SOC) and soil organic matter (SOM). Moreover, the total nitrogen (N), SOC, OM, total phosphorus (P), and soil water content (SWC) presented higher values in the topsoil than the deep layers. Conclusions: The highest production of glomalin in disturbed forests is probably a response to degradation processes. This work is a contribution to expand knowledge about glomalin dynamics in forest soils of the Amazon rainforest and provides essential information for future soil ecosystem restoration practices in tropical forests.